The Global Design Ranking: A Case Study of Design Awards Phenomenon - Chun-Yuan Chen; Po-Hsien Lin; Yen-Yu Kang; Chih-Long Lin (MDPI AG, 2023)
This study explored two issues: (1) could the number of design awards represent the design level of a country? (2) If the design award is not suitable as criterion, is there a more appropriate one(s)? Beginning with the phenomenon that use the number of design awards as a benchmark for evaluating national design capabilities, its rationality through objective data is examined. The research reviews the existing mechanisms and attempts to establish a more comprehensive one through expert interviews and questionnaires. Six criteria were identified: international activity, designers' level, future trends, historical impact, lifestyle taste, and environment standards. When these criteria are used to evaluate a country's design level, the results are in line with the overall impression of design experts. Conversely, the framework based on the number of design awards leads to a significant gap. The results overturn the evaluation systems of design awards. In terms of academic contribution, through the establishment of a new mechanism, the lack of existing ones can be made up. In terms of practical implication, design stakeholders in various countries have a benchmark for inspection when trying to improve their design level or international reputation. The research provides reference for policy formulation and strategy development.